Efficacy of Leptin Supplementation on Nuclear Maturation and Fertilization Rate of Sheep Oocytes In Vitro - Riyuska, A.; Karja, N. W. K.; Setiadi, A. (Tropical Animal Science Journal, 2019)
The objective of this study was to determine the efficacy of leptin supplementation into maturation medium on nuclear maturation and fertilization rate of sheep oocytes. The maturation process was conducted using a tissue culture medium (TCM) 199 with four supplementation treatments of leptin namely 0 (control), 10, 50, and 100 ng/mL. Fertilization was conducted in the oocytes supplemented with 10 ng/mL and control using 5×106 mL-1 spermatozoa. At the end of maturation and fertilization processes, the oocytes were stained with 2% aceto orcein to determine nuclear maturation rate and pronuclear development. The results showed that the percentage of oocytes reaching metaphase II (MII) stage significantly increased in the oocytes supplemented with leptin at a dose of 10 ng/mL (P